1997
DOI: 10.1126/science.278.5336.260
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of a C-H Bond Activation Reaction in Room-Temperature Alkane Solution

Abstract: Chemical reactions that break alkane carbon-hydrogen (C-H) bonds are normally carried out under conditions of high temperature and pressure because these bonds are extremely strong (ϳ100 kilocalories per mole), but certain metal complexes can activate C-H bonds in alkane solution under the mild conditions of room temperature and pressure. Time-resolved infrared experiments probing the initial femtosecond dynamics through the nano-and microsecond kinetics to the final stable products have been used to generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
191
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(211 citation statements)
references
References 30 publications
16
191
1
1
Order By: Relevance
“…In the related [TpЈRh(CO)] system, flash photolysis studies indicated that the unsaturated metal fragment first binds to the hydrocarbon to form a -alkane complex, which then undergoes C-H oxidative cleavage in a second unimolecular reaction (23)(24)(25). Density functional theory calculations have confirmed the stability of an alkane complex of TpRh(CO) (26).…”
mentioning
confidence: 80%
“…In the related [TpЈRh(CO)] system, flash photolysis studies indicated that the unsaturated metal fragment first binds to the hydrocarbon to form a -alkane complex, which then undergoes C-H oxidative cleavage in a second unimolecular reaction (23)(24)(25). Density functional theory calculations have confirmed the stability of an alkane complex of TpRh(CO) (26).…”
mentioning
confidence: 80%
“…T here is considerable interest in sigma-bonded organometallic alkane complexes, particularly since they have been identified as key intermediates in the transition metal-mediated COH activation process (1)(2)(3). Although such complexes generally are very short-lived intermediates (4), they have been known for over 30 years.…”
mentioning
confidence: 99%
“…Subsequently, several examples of alkane complexes in solution have been reported, and studies on the mechanism of the COH activation process have clearly demonstrated the role of these complexes in oxidative addition reactions (1,8,9). Time-resolved infrared (TRIR) spectroscopy has proved to be a powerful tool for the study of metal carbonyl alkane complexes.…”
mentioning
confidence: 99%
“…The related chemistry of the RhðTp 3;5-Me ÞðCOÞ 2 [Tp 3;5-Me ¼ HBð3;5-dimethylpyrazolylÞ 3 ] complex has been studied (8,9), and photolysis of RhðTp 3;5-Me ÞðCOÞ 2 led to the ejection of a CO ligand and the formation of a monocarbonyl complex, which was rapidly solvated to form Rhðκ 3 -Tp 3;5-Me ÞðCOÞðRHÞ. This species then decayed to form the more stable Rhðκ 2 -Tp 3;5-Me ÞðCOÞðRHÞ complex, which is able to undergo C─H activation to the final oxidative addition product, Rhðκ 3 -Tp 3;5-Me ÞðCOÞðRÞH.…”
mentioning
confidence: 99%